2014
DOI: 10.1590/1807-3107bor-2014.vol28.0034
|View full text |Cite
|
Sign up to set email alerts
|

Mineral content of ionomer cements and preventive effect of these cements against white spot lesions around restorations

Abstract: This study evaluated the ion exchange at the material/enamel interface and the preventive effect of restorative materials submitted to cariogenic challenge against white spot. Restorations in enamel/dentin of bovine teeth were performed with composite resin (Filtek™ Z250 -control group) and glass-ionomers cements -GICs (Ionomaster R™ and Fuji IX™ -experimental groups). Samples were grouped and submitted to neutral saliva (n = 15) or pH-cycling regimen (n = 15). After eight days of pH cycling, material/enamel i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…GICs have often been referred to as “smart materials” as they have a number of properties which may be altered in a controlled fashion in response to stimuli. These include ion exchange and recharge between the GIC and external environment, chemical adhesion to tooth enamel and dentin and a thermal expansion coefficient which is similar to teeth [ 35 37 ]. GICs also allow the incorporation of bioactive molecules including fluoride, strontium, calcium and phosphate that can be released to extend the influence of the material beyond its boundaries [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GICs have often been referred to as “smart materials” as they have a number of properties which may be altered in a controlled fashion in response to stimuli. These include ion exchange and recharge between the GIC and external environment, chemical adhesion to tooth enamel and dentin and a thermal expansion coefficient which is similar to teeth [ 35 37 ]. GICs also allow the incorporation of bioactive molecules including fluoride, strontium, calcium and phosphate that can be released to extend the influence of the material beyond its boundaries [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…GICs also allow the incorporation of bioactive molecules including fluoride, strontium, calcium and phosphate that can be released to extend the influence of the material beyond its boundaries [ 27 ]. Previous studies have shown that GICs are capable of remineralising carious tissue due to their high content of apatite forming ions and can prevent secondary caries lesions through ion release and chemical bonding properties with tooth enamel [ 37 ]. Al Zraikat et al .…”
Section: Discussionmentioning
confidence: 99%
“…12 In vitro studies used the pHcycling model to mimic the effect of oral conditions on the surface of restorative materials. [13][14][15][16][17] This model is characterized by the dynamics between periods of demineralization and remineralization, simulating a cariogenic challenge 17,18 proposed for laboratory studies by Featherstone and others 19 and modified by Serra and Cury. 20 On this research line, studies examined restorative materials such as glass ionomers and polyacid-modified resins throughout the pH cycling.…”
Section: Introductionmentioning
confidence: 99%
“…20 On this research line, studies examined restorative materials such as glass ionomers and polyacid-modified resins throughout the pH cycling. 13,15,16 Other studies submitted composite resins to pH cycling and analyzed their effect on the materials' surface after simulated toothbrushing. 14,17 Modification of surface roughness occurred when composite resin was submerged in different acidic solutions, with pH values ranging between 6.6 and 2.5.…”
Section: Introductionmentioning
confidence: 99%
“…This material has a very important role in clinical pediatric Brazilian Research in Pediatric Dentistry and Integrated Clinic 2014, 14(4):267-274 dentistry, with its main indication stemming from the material's adhesiveness to the dental structure, coefficient of linear thermal expansion similar to the tooth's, biocompatibility, and liberation of fluoride [34,35]. Because pediatric patients are less able to control caries, the liberated fluoride has the ability to remineralize the dental structure and stop the caries process [36].…”
Section: Discussionmentioning
confidence: 99%